Development of the ideas of labor and economic education of pupils in the modern conditions - S. N. Lyapakh (Вестник Северо-Кавказского федерального университета)
The article offers a view on the development of the ideas of labour and economic training under the current circumstances, as well as a possibility and need to integrate them into the training offered at schools nowadays.